IMPLEMENTATION OF INNOVATIVE MARKETING INTO THE ACTIVITIES OF INDUSTRIAL ENTERPRISES - SYSOIEVA, Inna; TSIKHANOVSKA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Innovative marketing is a process aimed at finding new business directions, creating fundamentally new products, and introducing innovations into the production of existing products. In practical terms, this involves the production and sale of competitive innovative products that fully meet the needs of consumers.The use of innovative approaches in the marketing activities of industrial enterprises makes it possible to better satisfy the needs of customers, increase the customer audience and master new sales markets. It has been studied that innovations reflect the technical, production and commercial potential of the enterprise, as well as its creative capabilities.The main driving factors for the development of innovative activities of industrial enterprises are competition, the growth of scientific and technical potential, changes in consumer behavior and dynamic processes of globalization.Innovations in marketing cover the improvement of product manufacturing processes, updating and improving their design, packaging, promotion methods, sales promotion and setting optimal prices for products.In the course of the study, the classification of marketing innovations according to general and specific characteristics based on their influence on the behavior of social groups was considered. All types of innovations are closely interconnected, forming a single system of innovative marketing.  The combination of different innovative approaches leads to changes in the marketing complex of the enterprise.It is noted that strategies based on modern technologies and aimed at developing new markets have a high level of risk.They require considerable effort in both marketing and technology areas, including making informed decisions in the development and implementation of strategies in such aspects as product policy, pricing, promotion methods, advertising activities and the selection of target markets.Choosing a strategy should take into account the company's strengths and weaknesses, its opportunities and threats, as well as resource potential, market positions and strategic goals.
Keywords: innovative marketing; innovations; efficiency; business success; consumer needs; demand; requests of society; marketing innovations; market; enterprise; strategy